BORC Functions Upstream of Kinesins 1 and 3 to Coordinate Regional Movement of Lysosomes Along Different Microtubule Tracks - Guardia, Carlos M. (Cell Rep, 2016)
The multiple functions of lysosomes are critically dependent on their ability to undergo bidirectional movement along microtubules between the center and the periphery of the cell. Centrifugal and centripetal movement of lysosomes is mediated by kinesin and dynein motors, respectively. We recently described a multisubunit complex named BORC that recruits the small GTPase Arl8 to lysosomes to promote their kinesin-dependent movement toward the cell periphery. Here we show that BORC and Arl8 function upstream of two structurally distinct kinesin types: kinesin-1 (KIF5B) and kinesin-3 (KIF1Bβ and KIF1A). Remarkably, KIF5B preferentially moves lysosomes on perinuclear tracks enriched in acetylated α-tubulin, whereas KIF1Bβ and KIF1A drive lysosome movement on more rectilinear, peripheral tracks enriched in tyrosinated α-tubulin. These findings establish BORC as a master regulator of lysosome positioning through coupling to different kinesins and microtubule tracks. Common regulation by BORC enables coordinate control of lysosome movement in different regions of the cell.